Active alkaline traps to determine acidic‐gas ratios in volcanic plumes: Sampling techniques and analytical methods. (14th July 2014) - Wittmer, J.; Bobrowski, N.; Liotta, M.; Giuffrida, G.; Calabrese, S.; Platt, U.
Abstract In situ measurements have been the basis for monitoring volcanic gas emissions for many years and—being complemented by remote sensing techniques—still play an important role to date. Concerning in situ techniques for sampling a dilute plume, an increase in accuracy and a reduction of detection limits are still necessary for most gases (e.g., CO2, SO2, HCl, HF, HBr, HI). In this work, the Raschig‐Tube technique (RT) is modified and utilized for application on volcanic plumes. The theoretical and experimental absorption properties of the RT and the Drechsel bottle (DB) setups are characterized and both are applied simultaneously to the well‐established Filter packs technique (FP) in the field (on Stromboli Island and Mount Etna). The comparison points out that FPs are the most practical to apply but the results are error‐prone compared to RT and DB, whereas the RT results in up to 13 times higher analyte concentrations than the DB in the same sampling time. An optimization of the analytical procedure, including sample pretreatment and analysis by titration, Ion Chromatography, and Inductively Coupled Plasma Mass Spectrometry, led to a comprehensive data set covering a wide range of compounds. In particular, less abundant species were quantified more accurately and iodine was detected for the first time in Stromboli's plume. Simultaneously applying Multiaxis Differential Optical Absorption Spectroscopy (MAX‐DOAS) the chemical transformation of emitted bromide into bromine monoxide (BrO) from Stromboli and Etna was determined to 3–6% and 7%, respectively, within less than 5 min after the gas release from the active vents.